Gangguan Metabolik pada Sindrom Ovarium Polikistik Nonklasik: Sebuah Laporan Kasus - Yogi Haditya; I Made Pande Dwipayana (MEDICINUS, 2026)
Polycystic ovary syndrome (PCOS) is the primary cause of both menstrual irregularity and androgen excess in women. PCOS can be diagnosed when women present with the classic features of hirsutism, irregular menstrual cycles, andpolycystic ovarian morphology on ultrasound. Women with PCOS, as compared with age- and body mass index-matched women without the syndrome, appear to have a higher risk of insulin resistance, hyperinsulinemia, glucose intolerance,dyslipidemia, and an increased prothrombotic state. These factors may result in higher rates of type 2 diabetes mellitus, fatty liver disease, subclinical atherosclerosis, vascular dysfunction, and ultimately cardiovascular disease and mortality. This case report presented a patient with hirsutism and prolonged menstrual cycles despite the absence of polycystic ovary on diagnostic investigation. Laboratory findings showed high cholesterol, triglycserides, and HbA1c level with a normal testosterone level. The primary management for this patient includes metformin to treat the insulin resistance and statin for the management of dyslipidemia.